Analysis of Colombia S Telemedicine Development, the Postconflict Potential Opportunity - Rodriguez-Garcia, A (Mary Ann Liebert Inc., 2020)
Aims: The goal of this study was to evaluate the development of telemedicine in Colombia. Materials and Methods: Searched for laws in the Colombian legal system; the statistics of services and health operators was extracted from the unique system of habilitation; we looked for reports from the Ministry of Information and Communication Technologies (ICT), the demographic statistics was obtained from the National Administrative Department of Statistics. Data analysis techniques were applied to identify possible relationships between them. Results: In Colombia, since the proclamation of the legality of telemedicine in 2007, there are five laws, five resolutions, and three government plans. A total of 3,245 services have been implemented in telemedicine, distributed throughout the territory by 51,490 operators, the ICT penetration rate is 21.17% by fixed internet and 39.3% by mobile internet; the Colombian population is 49,882,091 people, 25,228,444 women and 24,605,796 men, who are distributed 76.97% in the urban sector and 23.02% in the rural sector, and the coverage of health services is 94.8%. Conclusion: The development of health services in the telemedicine modality has been driven by Colombian regulations since 2007 and the plans for the growth of ICT infrastructure since 2009; however, these services have not yet reached 100% of the territory, especially areas with difficult access. The Colombian peace agreement creates the National Rural Health Plan (PNSR), which is presented as the obligation to carry out health coverage in all the territories, especially those in the rural areas, for the implementation of the strategy related to the implementation of services in telemedicine. © 2020, Mary Ann Liebert, Inc., publishers.
Keywords: telemedicine; development; health services; ICT coverage